(untitled) (International Journal of Environmental Sciences, 2025)
This paper explains the optimization of quantitative parameters for thermoelectric machining of magnesium based metal matrix composite. Sample prepared by stir casting method using Al2O3p (3%wt) and SiCp (6%wt) as reinforcement. CNC wire cut EDM used for machining as per DoE developed using RSM-BBD approach. Input parameters Pulse on, pulse off time, current and wire speed was varied to obtain machining efficiency and surface quality. Experimental models are developed and justified by ANOVA for optimization and response plots depicting optimized parameters of higher metal removal rate and lower roughness. Current and wire speed played significant role in obtaining the optimum values of input parameters. Higher value of MRR is obtained at Ton=18µs, Toff=7µs, I=1A & WS=10.40m/sec while lower value of roughness is obtained at Ton=6µs, Toff=7µs, I=1A & WS=6.76m/sec. DoE based RSM-CD approach for multi objective optimization depicts combination of optimal input parameters Ton=6µs, Toff=5µs, I=1.2A & WS=10.4m/sec for high MRR (0.153128 mm3/sec) and lower surface roughness (Ra=2.98165µm).